Ácido ascórbico na produção in vitro de embriões bovinos - Pozzobon, Sandra Elisa (2008)
In vitro cultured bovine embryos are susceptible to oxidative stress caused by high oxygen concentration, that contributes to free radicals formation. Therefore, antioxidant defense systems are needed to neutralize the reactive oxygen species and their harmful effects. The aim of this study was to evaluate the addition of different concentrations (100, 250 and 500μM) of ascorbic acid (AA) antioxidant to in vitro maturation (IVM, 9 replications) or culture (IVC, 8 replications) media of bovine embryos (Chapter 1). The concentration that provided greatest embryonic development rate and better embryo quality was added to in vitro maturation and/or culture media at different gaseous atmospheres (Chapter 2, 10 replications). Media without antioxidant served as control-groups. Cumulus-oocyte complexes obtained from bovine ovaries at the slaughterhouse were randomly distributed in groups and matured in TCM-199 with addition of pFSH, bLH and 10% estrus cow serum (ECS), for 22 to 24h, in an incubator at 39°C and 5% CO 2 in air and saturated humidity. The in vitro production was performed using 20-40 oocytes/group in 400μL of medium in 4-well dishes (Chap. 1) and 13-32 oocytes/group in 200μL drops of medium under mineral oil (Chap. 2). The in vitro fertilization (D0) was performed with Bos taurus taurus frozen semen selected by Swim-up (Chap. 1) and Percoll gradient (Chap. 2) with 1x106 spermatozoa/mL in TALP-Fert with heparin and PHE, for 18 to 22h, at the same IVM conditions. The presumptive zygotes were in vitro cultured in SOFaaci medium with 5% ECS under mineral oil, in the bag system at 5% CO2, 5% O2 and 90% N2 and saturated humidity (Chap. 1 and 2), or in an incubator at 5% CO2 in air and saturated humidity (20% O2 in air; Chap 2). To analyze the percentage of embryos on D2, D7 and D9 a randomized block delineation was used, having as blockade criteria the collection day (Chap. 1). In Chap. 2, the cleavage rate on D2 was analyzed considering the effects of AA addition on maturation and culture and the interaction between the two factors. The embryonic development data on D7 and D9 were analyzed after arc sine square root transformation and considered the effects of AA presence on maturation and culture, the gaseous atmosphere and the interaction among these factors, taking into account the routine day in the analyses model. Blastocyst cell number was obtained after base 10 logarithmic transformation of data, using 8 (Chap. 1) and 10 replications (Chap. 2), with a significance level of 5%. In Chapter 1, the cleavage rate and embryonic development on D7 were similar (P>0.05) among the different AA concentrations added to IVM or IVC. However, the 100μM AA addition to IVC tended (P<0.07) to show higher blastocyst production (32.3%) when compared to the 500μM group (19.7%). The blastocyst production on D9 increased significantly when 100μM AA were added to IVM (P<0.05) compared to control-group (38.7 vs 29.0%), or on IVC (P<0.01) compared to 500μM concentration (28.1 vs 14.1%). The blastocyst cell number was similar (P>0.05) among the different AA concentrations and the control-group. In Chapter 2, there was no effect of interaction (P>0.05) among the factors studied (AA on IVM, AA on IVC and atmosphere of culture) on D2, D7 and D9. Cleavage rate and embryonic development on D7 and D9 did not differ (P>0.05) between groups with and without antioxidant addition, independently of the gaseous atmosphere. However, a greater cell number was observed in hatched blastocysts (P<0.05) when the AA was included in the culture medium. The results indicate that 100μM ascorbic acid concentration can be used during IVM or IVC to increase embryo production, especially on D9, and improve the quality of hatched blastocysts, independently of the culture gaseous atmosphere.